Sustainable Development Research in the Asia-Pacific Region Education, Cities, Infrastructure and Buildings (World Sustainability Series,, 2018)
This multidisciplinary book focuses on best practices in sustainability research in the Asia-Pacific Region. Drawing links between research, practice, education for sustainability and the needs of industry, it addresses the sustainable development goals (SDGs). The book also presents research undertaken by a wide range of universities on matters related to sustainable development, in order to promote research in this area across multiple disciplines. Four key themes are explored: (1) Education for Sustainability. (2) Sustainable Cities. (3) Sustainable Buildings. (4) Sustainable Infrastructure. This unique book documents and disseminates the wealth of know-how on sustainable development research in the Asia-Pacific Region today. It presents lessons learned and comparative case studies from various countries, including India, China, Indonesia, the Philippines, Bangladesh, New Zealand and Australia.